1994
DOI: 10.1063/1.357909
|View full text |Cite
|
Sign up to set email alerts
|

Schottky diodes with high series resistance: Limitations of forward I-V methods

Abstract: Some methods have been proposed to deduce the value of Schottky parameters from forward I-V characteristic even in the presence of a large series resistance. In this paper, some well-known methods have been applied to experimental data of a real diode and to computer calculated curves. A comparison is made between these methods and the standard procedure. Some indications are given on the validity and the main limitations of all these techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(73 citation statements)
references
References 16 publications
3
68
0
2
Order By: Relevance
“…This dependence will make an error into accuracy of determining the ideality factor and, therefore, the barrier height, which is substantially greater than the error introduced by the measurement inaccuracy. Typical local maximum n for low voltages and increase of the ideality factor with the voltage at high voltages were observed by several authors [3,7,21,22].…”
Section: Calculation Of Barrier Parameters From Current-voltage Charamentioning
confidence: 89%
See 2 more Smart Citations
“…This dependence will make an error into accuracy of determining the ideality factor and, therefore, the barrier height, which is substantially greater than the error introduced by the measurement inaccuracy. Typical local maximum n for low voltages and increase of the ideality factor with the voltage at high voltages were observed by several authors [3,7,21,22].…”
Section: Calculation Of Barrier Parameters From Current-voltage Charamentioning
confidence: 89%
“…Carried out in the work by Aubry and Meyer [3] was a comparative analysis of the methods by Lien and Werner, and it was shown that the methods have mathematically similar procedures, accordingly, their accuracy and limitations are close.…”
Section: Calculation Of Barrier Parameters From Current-voltage Charamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, with a Schottky diode, the current-voltage (I-V) characteristic curve is commonly used to estimate the diode parameters, such as the barrier height (Φ b ), saturation current (I s ), ideality factor (η), parasitic series resistance (R s ) etc. [1][2][3]. In that the variation of differential conductance (δ G = dI/dV ) with respect to the bias voltage is used in estimating Schottky diode parameters [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Solar cell and panel circuit parameters are conventionally extracted from either the load I-V and P-V data measured under illumination or in the dark. Several methods for solar cell parameter extraction using the I-V and P-V characteristics have been proposed [1][2][3][4][5][6][7][8][9][10][11]. The direct approaches are based on the use of the I-V and P-V curve features such as the axis intercepts and the gradients at selected points to determine some of the cell parameters.…”
Section: Introductionmentioning
confidence: 99%